"Our interventions are still here to support communities during the pandemic": Resuming mass drug administration for neglected tropical diseases after COVID-19 implementation delays. - Tikhala Itaye; Sultani Hadley Matendechero; Jean Bosco Mbonigaba; Fikre Seife Gebretsadik; Tuduetso L Molefi; Gilbert Baayenda; Eugene Ruberanziza; Karsor K Kollie; January Zilabumba; Massitan Dembele; Kebede Deribe; Elia Muhima Adrien; et al. (PLoS Neglected Tropical Diseases)
The COVID-19 pandemic disrupted essential health services, including those provided by national neglected tropical disease (NTD) programs. Most mass drug administration (MDA) programs were postponed for 6-12 months following World Health Organization guidance released in April 2020 to temporarily halt NTD programs and launch necessary COVID-19 precautions. While NTD-endemic countries have since resumed MDA activities, it is critical to understand implementers' perspectives on the key challenges and opportunities for program relaunch, as these insights are critical for maximizing gains towards disease control and elimination during public health emergencies. Using data from using online surveys and focus group discussions, this mixed-methods study sought perspectives from Ministry of Health NTD Program Managers and implementing partners from non-governmental organizations working in sub-Saharan Africa. Data analysis revealed that findings converged around several main themes: disruptions for MDA programs included resource shortages due to prioritization of pandemic response, challenges adhering to COVID-19 safety protocols, and community hesitancy due to coronavirus transmission fears. Identified solutions for restarting MDA programs focused on adapting intervention delivery and packaging to minimize disease transmission, embracing technology to optimize intervention planning and delivery, and identifying opportunities to promote program integration between pandemic response strategies and NTD campaign delivery. Findings identifies key challenges due to disruptions to NTD program delivery and provide strategic recommendations for endemic countries to build resilient programs that can continue to perform during and beyond global pandemics.